Implementation of Children's Literature to Enhance Literacy in Primary Schools - Sukma, Elfia; Susanti, Nelly; Rinadevi, Rinadevi; Yani, Meri (STAI Miftahul Ula Nganjuk, 2024)
This study aims to investigate the implementation of children's literature in enhancing literacy among primary school students. Using children's literature as a literacy medium represents a strategic effort to foster students' reading interest. The study adopts a qualitative descriptive approach, collecting data through observations and questionnaires distributed to educators in various regions. The findings indicate that literacy activities employing children's literature as a medium have been implemented in primary education settings, particularly in lower-grade classes. Interviews with educators in Cluster III of the Palembayan District further confirm that children's literature effectively stimulates students' reading interest. These results underline the potential of children's literature as an innovative tool to support literacy development in primary schools.